EFL STUDENTS' PERCEPTION ON THE USE OF A MOBILE LEARNING APPLICATION “ENGLISH VOCABULARY” IN VOCABULARY LEARNING - Risnawati, Novi; Hidayat, Muhamad Taufik; Dewi , Sinta; Sharma, Prayash (English Education and Applied Linguistics Journal (EEAL Journal), 2023)
In today's era, technology permeates every aspect of daily life, including the field of education. There is a concept in education known as mobile assisted language learning (MALL). One instance of its application is the usage of mobile learning applications for vocabulary learning. This study was conducted to find out students' perceptions regarding the use of mobile learning applications (English Vocabulary) in learning vocabulary. Using the qualitative method, the researcher conducted interviews with five high school students who were selected purposively. The results showed that all participants felt helped by the mobile learning application during the learning vocabulary. Besides being easy to use, this application has various fun features that allows students to have pleasant learning. More into this, the students agree that the application should cover more complete material such as grammar, tenses and conversation. The study's findings suggest that mobile learning can assist students learn vocabulary, particularly when there is a pronunciation guide